The Meaning The Meaning of Nyambut Padi Baru Dance in the Dayak Kebahan Tribe as a Form of Relationship with Jubata : (Philosophical Review of Armada Riyanto's Philosophy of Relationality) - Mardani, Fransiskus Andreas; Cahyawicaksa, Yohanes Kukuh (Litbang STFT Widya Sasana Malang, 2025)
Nyambut Padi Baru dance is one of the regional dance forms of the Dayak Kebahan tribe, Poring, West Kalimantan. This dance implicitly shows the relationship between the Dayak Kebahan people and Jubata. This dance is usually performed during the Gawai Dayak ceremony or the harvest party of the Dayak Kebahan indigenous people. This research explores the philosophical values of the Nyambut Padi Baru dance of the Dayak Kebahan indigenous people by explaining the meaning and relationship between the Kebahan tribe and Jubata in Armada Riyanto‘s philosophy of relationality. This research uses a literature study by exploring articles, journals, and proceedings related to the theme of discussion. The results of this study show that the Nyambut Padi Baru dance of the Kebahan tribe has a meaning as a form of the community‘s gratitude relationship to Jubata for the harvest they received. The gratitude is expressed through a dance depicting the joy and joy of the community for the harvest.